In vitro capsaicin production by immobilized cells and placental tissues of Capsicum annuum L. grown in liquid medium - Johnson, T.S.; Ravishankar, G.A.; Venkataraman, L.V.
Capsaicin, from green pepper fruits is used in formulated foods and in pharmaceuticals. Cell cultures of Capsicum annuum L. were obtained from seedlings on Murashige and Skoog (MS)medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4- D)and kinetin. In vitro-grown cells and placental tissues from fruits were immobilized in calcium alginate. Immobilized cells and placental tissues produced capsaicin which leached out into the medium. Immobilized placental tissue exhibited greater potentiality for capsaicin synthesis than immobilized cells. Production reached a level of 1345 ~g eapsaicin g-~ of immobilized placenta on the 14th day of culture. Production of capsaicin, on replenished nutrient medium in immobilized placenta was 2400 ~g on the 30th day. Ferulic acid fed to immobilized placenta at 2.5 mM level increased capsaicin production by 2-fold by the 5th day of the culture period. Of the elicitors used, curdlan was effective on eapsaicin production in immobilized cells. Extracts of Aspergillius niger and Rhizopus oligosporus stimulated capsaicin production in immobilized placental tissues.
Keywords: CAPSICUM ANNUUM; CAPSAICIN; ELICITORS; IMMOBILIZED CELLS; PLACENTAL TISSUE; PRECURSORS